Subjective and objective interpretation of tear film interferometry images - Sharma, Nikhil; Oliver, Katherine (International Journal of Research in Medical Sciences, 2018)
Background: Assessment of the tear film is necessary in routine clinical practice because an unstable tear film can hamper the quality of life by causing vision-related problems and compromising the ocular surface. One of the major concerns related to an unstable tear film is dry eye. Many of dry eye patients suffer from a lack of meibum which forms the lipid layer of the tear film. The lipid layer can be graded and interpreted by using interferometry. However, interpretation and grading of this dynamic layer may be inconsistent in terms of inter- and intra- observations. This study investigated the difficulty of consistent, subjective grading of clinical findings, in general. Methods: The interferometry images of 30 subjects captured from different equipment were analyzed subjectively. The agreement between intra-observer repeatability was also measured. Results: A positive Spearman’s correlation of 0.81 was found among different grading patterns observed using the Tearsope to compare right and left eyes. Similarly, a positive Spearman’s correlation of 0.63 was found among different grading patterns observed under interferometer in right and left eye. Correlations were statistically significant, p<0.001. The agreement between intra-observer repeatability calculated using Cohen’s kappa values were also statistically significant, p<0.001. Conclusions: A correlation between the findings of different equipment could not be made due to the differences in wavelengths of incident light and the image details. However, a new grading pattern has been proposed to describe the thickness of various lipid layer patterns observed under Doane’s interferometer.